2016
DOI: 10.1097/lgt.0000000000000085
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Sexual Dysfunction in a Vulvovaginal Specialty Clinic

Abstract: Objective Our study evaluated the presence and predictors of sexual dysfunction in a vulvovaginal specialty clinic population. Materials & Methods Women who presented to a vulvovaginal specialty clinic were eligible to enroll. Participants completed a questionnaire, including Female Sexual Function Index (FSFI) to assess sexual dysfunction and Patient Health Questionnaire (PHQ)-9 depression screen, and underwent a standardized physical exam, with vaginal swabs collected for wet mount and culture. Logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
1
15
0
4
Order By: Relevance
“…From the researcher point of view this similarity as education becomes basic need in all different social layers. In this current study reported that half of cases get their menarche was (13)(14) and with duration (3)(4)(5) days, this study is supported by Koseoglu (2016) this study title was" Is There Any Impact of Copper Intrauterine Device on Female Sexual Functioning'' In this cross-sectional study subjects were divided into two groups IUD users group was nearly half and control group was nearly half. Both two gropes started their menarche between age (12)(13)(14) years with duration (3-5) days.…”
Section: Discussionsupporting
confidence: 61%
“…From the researcher point of view this similarity as education becomes basic need in all different social layers. In this current study reported that half of cases get their menarche was (13)(14) and with duration (3)(4)(5) days, this study is supported by Koseoglu (2016) this study title was" Is There Any Impact of Copper Intrauterine Device on Female Sexual Functioning'' In this cross-sectional study subjects were divided into two groups IUD users group was nearly half and control group was nearly half. Both two gropes started their menarche between age (12)(13)(14) years with duration (3-5) days.…”
Section: Discussionsupporting
confidence: 61%
“…Lichen planus (LP) is a chronic inflammatory dermatosis that affects skin, mucous membranes, and nails . A multidisciplinary vulvar clinic study highlighted a prevalence of 3.7% for biopsy‐proven vulvar LP (VLP) . In our study, we found a slightly higher prevalence of 5.8% for biopsy‐proven VLP.…”
Section: Discussionmentioning
confidence: 46%
“…In our study, we found a slightly higher prevalence of 5.8% for biopsy‐proven VLP. The cause of LP is not completely established . Vulvovaginal gingival (VVG) syndrome is a subtype of LP in which disease affects the vulva, vagina, and gingival margins .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common disorders triggering sexual dysfunction are vulvar infections, lichen and vulvodynia. Women with vulvar disorders have less frequent and less satisfying sexual activity [40,41].…”
Section: Impact Of Vulvar Disorders On Sexual Functionmentioning
confidence: 99%